Damage Control Resuscitation Protocol and the Management of Open Abdomens in Trauma Patients. Issue 8 (August 2014) - Bradley, Matthew; Galvagno, Samuel; Dhanda, Amit; Rodriguez, Carlos; Lauerman, Margaret; Dubose, Joseph; Scalea, Thomas; Stein, Deborah
Although the use of damage control laparotomy (DCL) is well established, the effect of damage control resuscitation (DCR) on the management of open abdomens is relatively poorly studied. The aim of the present study was to determine the predictors for failure to achieve primary fascial closure (PFC) after DCL in the setting of a massive transfusion (MT) and DCR. This is a retrospective review over a 12-year period of all patients that underwent MT and DCL. Patients who achieved PFC were compared with those who did not (NPFC). Student's t tests were used to compare the two groups. A multiple logistic regression model was performed to identify independent risk factors for failure to attain PFC. Of 174 patients, 101 achieved PFC. Mean (6 standard deviation) age was 35.6 ± 14.9 years for PFC and 36.3 ± 14.0 years for NPFC ( P = 0.75). Admission Glasgow Coma Scale score was 11.4 ± 4.6 for PFC and 10.6 ± 5.0 for NPFC ( P = 0.25). Initial lactate (7.3 ± 3.8 vs 7.7 ± 4.1, P = 0.50), hemoglobin (11.3 ± 1.9 vs 11.0 ± 2.2, P = 0.43), systolic blood pressure (108 ± 44 vs 107 ± 35, P = 0.82), Injury Severity Score (34 ± 14 vs 36 ± 15, P = 0.32), and abdominal Abbreviated Injury Score (3.6 ± 1.1 vs 3.9 ± 1.0, P = 0.13) were similar between the two groups. There was no difference in total blood products administered at 24 hours (46 ± 26 vs 49 ± 29 units, P = 0.45). Logistic regression identified increasing volume of crystalloid at 24 hours (odds ratio, 0.86; 95% confidence interval, 0.74 to 0.99; P = 0.047), earlier operative year (2.1; 1.52 to 2.91; P < 0.001), and increased number of procedures (0.32, 0.18 to 0.58; P < 0.001) as independent predictors for failure to obtain PFC. Injury severity is not associated with failure to achieve PFC, whereas administration of large-volume crystalloid resuscitation, increasing number procedures, and earlier year of DCL are independent predictors for failure to achieve PFC. Application of DCR to DCL techniques results in an improvement in ability to achieve PFC.